Transformation in soil and availability to plants of 15N applied as inorganic fertilizer and grass residue (Journal of Science and Technology, 2016)
A pot experiment was conducted in the glasshouse at the Imperial College at Wye to study the transformations that occur following application of both inorganic and organic nitrogen (N) leading to availability to maize and losses into the environment. Organic N was applied as winter rye residue at the rate of 20 g per pot, whilst inorganic N was applied as double-labeled 15NH415NO3 (5 atom %) at the rate of 100 and 200 kg ha-1. Watering was done when the soil began to dry up. Results indicate that N uptake by maize was affected by the rate and source of N application. Seventy-nine days after fertilizer application, 33 % of the N applied at 100 kg ha-1 was recovered in maize, but this was reduced to 24 % when the N application rate was doubled. Of the total N applied in the enriched rye residue, maize N recovery was 20.9 %, soil recovery was 53.2 %, and 0.002 % was lost through N2O emission. By difference, the amount unaccounted for, 25.89 %, was presumably either leached out of the pots and/or incorporated into the soil microbial biomass.